2015
DOI: 10.18632/oncotarget.6681
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of SET7/9, a histone mono-methyltransferase, is associated with gastric cancer progression

Abstract: SET7/9, a histone methyltransferase, has two distinct functions for lysine methylation. SET7/9 methylates non-histone proteins, such as p53, and participates in their posttranslational modifications. Although SET7/9 transcriptionally activate the genes via H3K4 mono-methylation, its target genes are poorly understood. To clarify whether or not SET7/9 is related to carcinogenesis, we studied alterations of SET7/9 in gastric cancers (GCs). Among the 376 primary GCs, 129 cases (34.3%) showed loss or weak expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 44 publications
(58 reference statements)
2
38
0
Order By: Relevance
“…Diverged expression patterns and functions of SET7/9 in different cancer types have been reported. SET7/9 acts as a tumor suppressor in breast cancer and gastric cancer with down-regulated expression in tumor tissues 1 , 15 . However, SET7/9 shows increased expression in prostate cancer and hepatocellular carcinoma and promotes cell proliferation by regulating cell cycle 19 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diverged expression patterns and functions of SET7/9 in different cancer types have been reported. SET7/9 acts as a tumor suppressor in breast cancer and gastric cancer with down-regulated expression in tumor tissues 1 , 15 . However, SET7/9 shows increased expression in prostate cancer and hepatocellular carcinoma and promotes cell proliferation by regulating cell cycle 19 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, SET7/9 shows increased expression in prostate cancer and hepatocellular carcinoma and promotes cell proliferation by regulating cell cycle 19 , 30 . It is thus suggested that SET7/9 may play distinct roles in tissue- and cancer-specific manners 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This histone methyltransferase (HMT) enzyme is known to catalyze the mono-methylation of H3K4 and is also associated with the methylation of non-histone proteins including p53. The role of this HMT in carcinogenesis is controversial as some studies report its tumor suppressor function [67,68] while others associate its activity with increased proliferation [69]. Overall, among all di-and tri-methylated lysines on histone H3 that we examined (K36me2/me3, K4me2/me3, K79me2/me3, K27me2/me3 and K9me2/me3), it was observed that only the expression levels of H3K4me3 were significantly reduced upon exposure to AITC.…”
Section: Discussionmentioning
confidence: 84%